An analysis of the LNG shipping market due to the energy crisis – an European context - Tan, Sher Ling (Nanyang Technological University, 2023)
The Russo-Ukrainian War has driven the Energy Crisis to befall on Europe. With the occurrence of an energy crisis, the European Union (EU) is seeking to address their energy security concerns to tide themselves through. This entailed diversification of European countries’, specifically the EU’s, energy sources to Liquified Natural Gas (LNG). The actions taken by European countries include sourcing LNG from other regions other than Russia and construction of LNG terminals and Floating Storage Regasification Units (FSRUs) within Europe to accommodate to an increase in LNG import. In LNG shipping, an increase in LNG carriers were also recorded. The focus of the study is to analyze the LNG shipping market amidst the Energy Crisis and evaluate if the reliance of the EU on LNG was strategic. To determine whether the EU’s decision was strategic, consideration of LNG shipping’s demand in the future is to be analyzed to evaluate if the efforts by the EU will be sustained for the long term. Questionnaires and interviews were conducted to derive the sentiments of the LNG market by Maritime professionals amidst the ongoing energy crisis. The potential of LNG shipping has been inferred from maritime professionals within the industry. Based on the responses from the maritime professionals, energy security concerns, governmental regulations, technological advancements will potentially affect the demand of LNG, with challenges such as high investment costs, LNG safety risks, demand uncertainty and competition from renewables posing as challenges to adoption of LNG. Subsequently, the future sustainability of the LNG shipping market was then analyzed with regards to the above demand factors, challenges, and competitiveness of other alternative fuels. Concluding the study, the diversification of EU’s energy sources to LNG to other non-Russia regions is reviewed. Keywords: Energy crisis, liquified natural gas, LNG, energy resources